How well does education travel? Education and occupation with and without migration - August Gächter; Stefanie Smoliner (FIW - Research Centre International Economics, 2010)
Using the Labour Force Survey (LFS) we explore the difference international migration makes for the distribution of occupational levels for any given level of education in the two countries of interest: Austria and Germany. Migrant outcomes are also being compared with home country outcomes, i.e. Serbia and Turkey. We find that education is imperfectly portable across national borders. Austrian employers treat schooling from certain countries of origin differently from the way they treat schooling from natives. Educational levels completed in Western European countries are obviously more transferable across national borders than educational levels completed elsewhere. Workers in their home country all have similar occupational returns to education but migrants in Austria or Germany lag considerably behind. Middle and higher education in particular are not equally rewarded if from abroad. The low value of foreign-acquired education may reflect discrimination, differences in school quality across continents of origin, imperfect knowledge of the evaluation of foreign credentials on the side of the employer or the low compatibility of the foreign-acquired education with the requirements and the specific orientation of the host country labour market.
Keywords: J24; J71; 330; occupation; education; migration; labour force survey; Hauser-Warren score